Efficacy of Penile Low-Intensity Shockwave Therapy and Determinants of Treatment Response in Taiwanese Patients with Erectile Dysfunction - Kai-Yi Tzou; Su-Wei Hu; Oluwaseun Adebayo Bamodu; Yuan-Hung Wang; Wen-Ling Wu; Chia-Chang Wu (Biomedicines, 2021)
Background: Erectile dysfunction (ED) remains an emotional wrench to patients and a therapeutic challenge to urologists in andrology clinics worldwide. This is, in part, related to refraction to, or transient effect of phosphodiesterase 5 inhibitors (PDE5i), coupled with patients’ dissatisfaction with this treatment modality. Low-intensity extracorporeal shockwave therapy (Li-ESWT) is an evolving treatment option, with promising curative potential. Current international guidelines are inconclusive, bear weak recommendation strength, and lack ethnogeographic consensus. Objectives: This study evaluated the safety, efficacy, and effect duration of Li-ESWT, as well as exploring disease-associated determinants of treatment success in Taiwanese males with ED. Methods: A cohort of 69 eligible cases treated with 12 sessions of Li-ESWT and followed up for at least 12 months after treatment, between January 2018 and December 2019 at our medical facility, was used. The present single-center, retrospective, non-randomized, single-arm study employed standardized erectile function evaluation indices, namely, the five-item International Index of Erectile Function (IIEF-5) and Erection Hardness Score (EHS). Clinicopathological analyses of selected variables and comparative analyses of time-phased changes in the EF indices relative to baseline values were performed. Evaluation of treatment success was based on minimal clinically important difference (MCID), using a binomial logistic regression model. Results: The median age and duration of ED for our Taiwanese cohort were 55 years and 12 months, respectively, and an average of 31.3% presented with co-morbidities. The mean improvement in IIEF-5, EHS, and quality of life (QoL) domain scores relative to the baseline values was statistically very significant (p < 0.001) at all indicated follow-up time-points. When stratified, Taiwanese patients with severe and moderate ED benefited more from Li-ESWT, compared with those in the mild or mild-to-moderate group. Patients’ pre-Li-ESWT PDE5i response status was not found to significantly influence Li-ESWT response. Univariate analysis showed that age > 45 years (p = 0.04), uncontrolled diabetes mellitus (p = 0.04), and uncontrolled hyperlipidemia (p = 0.01) were strongly associated with Li-ESWT efficacy; however, only age > 45 years (p = 0.04) and uncontrolled hyperlipidemia (p = 0.03) were found to be independent negative predictors of Li-ESWT success by the multivariate logistic model. Follow-up was uneventful, with no treatment-related adverse events or side effects reported. Of the treated patients, 86.1% indicated satisfaction with the treatment regimen, and over 90% indicated they would recommend the same therapy to others. Conclusions: Li-ESWT is a safe and efficacious therapeutic modality for Taiwanese patients with ED. Uncontrolled hyperlipidemia and age > 45 years are independent negative predictors of treatment success for this cohort.